Internalisasi Moderasi Beragama melalui Pembelajaran Lapangan: Studi Pengalaman Mahasiswa pada Pameran Matakin di Medan - Husna Sari; Ilham Ramadhan Daulay; Muhammad Fadly Chaniago; Gus Salza Nazwa; Wiana Delviani; Siti Rahma; Muhammad hazil Ali Kahar (Al Iman: Jurnal Keislaman dan Kemasyarakatan, 2026)
This study aims to analyze the internalization of religious moderation values through field-based learning at an exhibition organized by the Majelis Tinggi Agama Konghucu Indonesia (MATakin) in Medan. The research employs a qualitative descriptive-reflective approach within a constructivist paradigm. The subjects consisted of six student interns who participated in the visit and interfaith dialogue with the Chairperson of MATakin Medan. Data were collected through participant observation, students’ reflective notes, documentation, and analysis of open dialogue sessions. The findings reveal that field-based learning effectively fosters both cognitive and affective transformation among students. Direct experience and dialogical interaction contributed to the reduction of stereotypes, enhancement of empathy, and strengthening of national commitment. The values of humanity and social harmony in Confucian teachings served as reflective bridges that deepened students’ understanding of religious moderation. These results indicate that the internalization of moderation values cannot rely solely on normative classroom instruction but requires contextual and dialogical engagement. Therefore, interfaith field learning may serve as a pedagogical model in higher education to reinforce social resilience and cultivate moderate character within plural societies. Penelitian ini bertujuan menganalisis proses internalisasi nilai moderasi beragama melalui pembelajaran lapangan pada pameran yang diselenggarakan oleh Majelis Tinggi Agama Konghucu Indonesia (MATakin) Kota Medan. Pendekatan yang digunakan adalah kualitatif deskriptif-reflektif dengan paradigma konstruktivis. Subjek penelitian terdiri atas enam mahasiswa peserta magang yang mengikuti kunjungan dan dialog lintas iman bersama Ketua MATakin Medan. Data dikumpulkan melalui observasi partisipatif, catatan reflektif mahasiswa, dokumentasi kegiatan, serta analisis dialog terbuka. Hasil penelitian menunjukkan bahwa pembelajaran lapangan efektif dalam membangun transformasi kognitif dan afektif mahasiswa. Pengalaman konkret dan dialog langsung berkontribusi pada reduksi stereotip, peningkatan empati, serta penguatan komitmen kebangsaan. Nilai kemanusiaan dan harmoni dalam ajaran Konghucu menjadi medium reflektif yang memperkaya pemahaman mahasiswa tentang moderasi beragama. Temuan ini menegaskan bahwa internalisasi nilai tidak cukup melalui pendekatan normatif di kelas, melainkan memerlukan pengalaman dialogis yang kontekstual. Dengan demikian, pembelajaran lapangan berbasis dialog lintas iman dapat direkomendasikan sebagai model pedagogis dalam pendidikan tinggi untuk memperkuat ketahanan sosial dan membangun karakter moderat di tengah masyarakat plural.